Samarium doped Sn15Sb85: a promising material for phase change memory applications. Issue 88 (11th December 2017) - Zou, Hua; Zhai, Liangjun; Hu, Yifeng; Zhu, Xiaoqin; You, Haipeng; Zhang, Jianhao; Song, Sannian; Song, Zhitang
Abstract : Thermal stability of phase change films is key for phase change memory applications. Sm doped Sn15 Sb85 thin films were prepared by magnetron sputtering. Compared with none doped films, the thermal stability of the film was significantly improved. Abstract : The thermal stability of phase change films is a key parameter in phase change memory (PCM) applications. Here, we find that the Sm doped Sn15 Sb85 films have a higher crystallization temperature and a better data retention ability in comparison with those of pure amorphous SnSb films, revealing a potential candidate for PCM applications. In addition, it demonstrated that the Sm doping was also propitious to reduce the power consumption and decrease the change of roughness in the crystallization process. Finally, the data storage capability of the Sm0.015 (Sn15 Sb85 )0.985 -based PCM cell was obtained with a reversible phase change process between high and low resistance states.